2015
DOI: 10.1055/s-0041-106538
|View full text |Cite
|
Sign up to set email alerts
|

Combination of Ultrasound-Guided Percutaneous Microwave Ablation and Radioiodine Therapy in Benign Thyroid Disease: A 3-Month Follow-Up Study

Abstract: Purpose: Pilot studies of combined therapies treating benign nodular goiters reported promising results. The aim of this study was to investigate the effectiveness of combined microwave ablation (MWA) and radioiodine therapy (RIT) with a special focus on thyroid function at the 3-month follow-up. Materials and Methods: 15 patients (median age: 55 years) with a large goiter and benign thyroid nodules or Graves? disease were treated with the combined therapy. Serum levels of triiodothyronine (T3), thyroxine (T4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 21 publications
1
16
0
1
Order By: Relevance
“…In 82% of index nodules, the decrease was >50%. Similarly encouraging results have been reported by other groups using this technique to ablate thyroid tissue with preservation of thyroid function, consistent volume reduction and low recurrence rates …”
Section: Benign Thyroid Nodulessupporting
confidence: 81%
“…In 82% of index nodules, the decrease was >50%. Similarly encouraging results have been reported by other groups using this technique to ablate thyroid tissue with preservation of thyroid function, consistent volume reduction and low recurrence rates …”
Section: Benign Thyroid Nodulessupporting
confidence: 81%
“…Two patients showed TSH levels below the normal range, but all patients were clinically euthyroid. No serious complications occurred, and the authors concluded the combination of MWA and RIT was "an effective approach for the treatment of large benign nodular goitres" [36].…”
Section: Discussionmentioning
confidence: 99%
“…The combination of a local ablative procedure with RIT could help make this treatment safer and available to a higher number of patients. The first approaches of combined therapy showed promising results [9,10,17,36]. An early prospective randomised study by Zingrillo et al from 2003 [10] described the combined therapy of PEIT and RIT in comparison to RIT single therapy in large (>4 cm) toxic thyroid nodules (TTNs).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As a relatively new technique for thyroid disease, US-guided MWA has been difficult for many patients with SSG to accept. In terms of the follow-up period, based on previous studies of thermal ablation for thyroid nodules, [28][29][30] although the reduction rate continuously increases over a few months, the greatest reduction of volume is achieved within the first few months. In addition, as the results show, at the 3-month follow-up, the major volume reduction and symptom relief had already occurred without complications or unexpected side effects.…”
Section: Discussionmentioning
confidence: 99%